FUNGOS FILAMENTOSOS ISOLADOS DO RIO ATIBAIA, SP E REFINARIA DE PETRÓLEO BIODEGRADADORES DE COMPOSTOS FENÓLICOS - Conceição, D. M. [UNESP]; Angelis, D. A. de [UNESP]; Bidoia, E. D. [UNESP]; Angelis, D. de F. De [UNESP] (Instituto Biológico, 2021)
Despite their wide distribution in nature, phenolic compounds are part of the main toxic pollutants discarded by the petrochemical, textile and other industries. Considering the environmental importance of these substances, filamentous fungi were selected aiming at their future use in biotreatment of residues. Two hundred and fifty-seven strains were isolated from the oil refinery effluent, and from the Atibaia river water. They were inoculated on a phenolic substrate to develop a degradation halo, which was measured and classified. A technique named Bavendamm Reaction was used to determine the enzyme activity of fungal phenoloxidases and peroxidases. The isolates were also cultivated in the effluent of the stabilization lagoon to study biomass production and their resistance. Results showed that 50% of tested isolates produced the enzymes studied and 80% was able to grow in the effluent. The isolates investigated presented an important potential to be used in bioremediation processes, for future application in the treatment of phenolic effluent residues.

Apesar de amplamente distribuídos na natureza os compostos fenólicos fazem parte dos principais poluentes tóxicos residuais descartados pela industria petroquímica, têxtil, entre outras. Considerando a importância ambiental destas substâncias, fungos filamentosos foram selecionados objetivando-se futuros biotratamentos de contaminantes. As 257 cepas fúngicas, isoladas do efluente da refinaria de petróleo e do rio Atibaia, SP, Brasil, foram cultivadas em ácido 3,4,5 trihidroxibenzóico, e o halo de degradação foi medido e classificado. A técnica denominada Reação de Bavendamm foi o recurso utilizado para determinar a atividade fenolítica. Cultivou-se também os isolados no efluente da lagoa de estabilização da refinaria para verificar a biomassa e a resistência. Os resultados demonstram que 50% das cepas testadas apresentam atividade fenolítica e 80% cresceram no efluente da refinaria de petróleo. Os fungos selecionados demonstraram potencial para serem introduzidos em processos de biorremediação, com perspectivas de resultados promissores para tratamentos de resíduos e efluentes fenólicos.
FILAMENTOUS FUNGI ISOLATED FROM RIO ATIBAIA, SP, BRAZIL AND OIL REFINERY FOUND TO BE BIODEGRADATERS OF PHENOLIC COMPOUNDS
Keywords: Biodegradation; Atibaia River; phenoloxidases; Bavendamm Reaction; filamentous fungi; oil refinery; Biodegradação; rio Atibaia; fenoloxidases; Reação de Bavendamm; fungos filamentosos; refinaria de petróleo